Economic Empowerment of Mothers Through Product Production Training: Case of Making Dishwashing Soap in Kadilangu Village - Andhika Shafa Anggara; Viki Uluwil Himmah; Melisa Mainatul Chasanah (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
This work program examines the economic activities, especially of mothers in Kadilangu Village, Kangkung District, Kendal Regency, where the majority of mothers' jobs there are farmers and housewives. Training on making dishwashing soap in Kadilangu Village was held involving community representatives, where two representatives from each RT were present from a total of 18 RTs in Kadilangu Village. The resource persons for this training were members of the MIT-18 KKN team Posko 120 UIN Walisongo, totaling 4 presenters with competencies in the field of chemistry. The training was carried out divided into six groups, where each group consisted of six members who would directly participate in soap making from the start until the product was ready to use. With these new skills, residents now have the potential to create an additional source of income after completing housework and rice field activities, which is also expected to improve the welfare of the family and community as a whole.